2016
DOI: 10.21608/ajfm.2016.18550
|View full text |Cite
|
Sign up to set email alerts
|

The immunotoxic effects of short term chronic exposure to Titanium Dioxide Nanoparticles on spleen of adult albino rats and the role of after toxic effect follow up

Abstract: The usage of Titanium Dioxide NanoParticles (TiO2NPs) on a large scale of applications was a reason of a variety of many health problems. The aim of the current study was to evaluate the immune toxic effects of short term administration of TiO2NPs on spleen. Material and Methods: Forty Adult male Rats were equally divided into four groups as follows: Group I: negative control, Group II: positive control, Group III: received TiO2NPs (1200 mg/kg) orally daily for 12 weeks. Group IV: follow up group received TiO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…By using different cell lines, numerous studies showed the ability of TiO2 NPs in inducing genotoxicity (Landsiedel et al, 2009;Singh et al, 2009;Turkez, 2011;Catalán et al, 2012;Ghosh et al, 2013;Tavares et al, 2014;Khan et al, 2015 andPatel et al, 2017). Also, multiple in vivo studies showed genotoxicity induced by TiO2NPs (Trouiller et al, 2009;Mohamed andHussien, 2016 andEl-Sheikh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…By using different cell lines, numerous studies showed the ability of TiO2 NPs in inducing genotoxicity (Landsiedel et al, 2009;Singh et al, 2009;Turkez, 2011;Catalán et al, 2012;Ghosh et al, 2013;Tavares et al, 2014;Khan et al, 2015 andPatel et al, 2017). Also, multiple in vivo studies showed genotoxicity induced by TiO2NPs (Trouiller et al, 2009;Mohamed andHussien, 2016 andEl-Sheikh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of El-Sheikh et al, who reported moderate improvement in the histopathological changes in rat spleens after the administration of TiO 2 NPs was ceased for 8 weeks. 44 There was a significant decrease in the mean epithelial thickness in group II (TiO 2 NPs) as compared to both group I and group III (p < 0.01 and p < 0.01, respectively). The fact that the epithelial thickness was almost back to normal after the recovery period, despite the marked atrophy, indicates notable basal cell proliferation to compensate for this cell loss.…”
Section: Discussionmentioning
confidence: 83%
“…Sections were stained with hematoxylin and dehydrated with ethanol and xylene. Immunostaining of CD4 were carried out by counting expression of CD4 on lymphocytes at 40x magnification (EL-Sheikh et al, 2016).…”
Section: Ii24 Immunohistochemical Staining For Cd4 In Spleenmentioning
confidence: 99%